Education, Earnings, and Inequality in Brazil, 1982-98 : Implications for Education Policy - Blom, Andreas (World Bank, Washington, DC, 2014)
The educational attainment of Brazil's labor force, has gradually increased over the past two decades. At the same time, the government has pursued a series of economic structural adjustment policies. The authors investigate how these simultaneous advances have altered the relationship between labor market earnings, and education. They find that the returns to education in the labor market, fundamentally changed between 1982, and 1998. While the returns to tertiary education increased sharply, the returns to primary education dropped by 26 percent, and those to lower secondary, by 35 percent. Moreover, the authors argue, the marginal reduction in wage inequality that occurred in this period was linked primarily to a reduction in the returns to schooling, and only secondarily, to a more equitable distribution of schooling. The findings suggest that the supply of highly skilled labor is inadequate to meet demand. That suggests a need for policy action aimed at increasing access to, and completion of tertiary education. Increasing the supply of highly skilled labor, would improve prospects for both economic growth, and reduce wage inequality.